THEMIS-A SCM Filter Bank Level-2 (CDF) - CDPP (CNES, 2022)
This dataset contains digitally computed Filter Bank spectra and E12 peak and average in HF band from the Search Coil Magnetometer (SCM) and the Electric Field Instrument (EFI) on board THEMIS-A.